The Test of Improvement Activity on Kidney Function by Etanolic Extract of Lansau from Muna Regency on Male Wistar Rat - Ruslin, R; Kasmawati, Henny; Suryani, S; Ihsan, Sunandar; Soleman, Imelda Sarda (Fakultas Farmasi Universitas Halu Oleo, 2020)
Lansau is one of the traditional ingredients that consist of 44 types of plants that are believed by the local society as a nutritious herb to treat various diseases that exist in the society of Muna Southeast Sulawesi Province that has been used for hundreds of years for generations. The study was conducted to determine the effect of ethanol extract of Lansau on the improvement activity of kidney function that induced gentamicin-piroxicam. A total of 24 rats were used in which 20 ratswere modeled with damage of renal function using gentamicin-piroxicam drug which was then grouped into 5 groups. The first group was treated using a Lansau extract with doseI , the second group was treated with aLansauextract dose II, the third group was treated with the Lansau extract dose III, the fourth group was treated with ketosteryl, the fifth group was no treatment only given Na. 1% CMC and the sixth group is the normal group. The Modeling was performed for 7 days and on the eighth day blood sampling was taken to measure creatinine and urea levels. As for therapy performed for 4 weeks and every end of the week also made blood taking for measurement of creatinine and urea. The highest percentage of creatinin decrease for each group was negative group -8.92%,positive group control was 84.21%,dose group I 74.75%, dose group II 80.07%, and dose group III 84.08%. For the highest percentage of decrease of ureum level for each group that is negative group -31.l49%,positive control group 49.59%,dose group I 40.53%, dose group II 26.79%, and dose group III 43.32%. The results showed that Lansau ethanol extract has the potential and effectiveness in the repair of kidney function damage.